Enhancing Heavy Metal Toxicity Assessment Through the Use of Ciliates as Cellular Bioindicators (International Journal of Food and Nutritional Sciences, 2022)
The assessment of heavy metal toxicity is of paramount importance in safeguardingenvironmental and human health. This study explores an innovative approach to enhance heavymetal toxicity assessment by employing ciliates, specifically Paramecium and Tetrahymenaspecies, as cellular bioindicators.